Asthma and COVID-19: review of evidence on risks and management considerations. Issue 4 (3rd September 2020) - Hartmann-Boyce, Jamie; Gunnell, James; Drake, Jonny; Otunla, Afolarin; Suklan, Jana; Schofield, Ella; Kinton, Jade; Inada-Kim, Matt; Hobbs, F D Richard; Dennison, Paddy
Abstract : Background: Respiratory illnesses typically present increased risks to people with asthma (PWA). However, data on the risks of COVID-19 to PWA have presented contradictory findings, with implications for asthma management. Objective: To assess the risks and management considerations of COVID-19 in people with asthma (PWA). Method: We conducted a rapid literature review. We searched PubMed, medRxiv, LitCovid, TRIP, Google and Google Scholar for terms relating to asthma and COVID-19, and for systematic reviews related to specific management questions within our review, in April 2020. References were screened and data were extracted by one reviewer. Results: We extracted data from 139 references. The evidence available is limited, with some sources suggesting an under-representation of PWA in hospitalised cases and others showing an increased risk of worse outcomes in PWA, which may be associated with disease severity. Consensus broadly holds that asthma medications should be continued as usual. Almost all aspects of asthma care will be disrupted during the pandemic due not only to limits in face-to-face care but also to the fact that many of the diagnostic tools used in asthma are considered aerosol-generating procedures. Self-management and remote interventions may be of benefit for asthma care during this time but have not been tested in this context. Conclusions: Evidence on COVID-19 and asthma is limited and continuing to emerge. More research is needed on the possible associations between asthma and COVID-19 infection and severity, as well as on interventions to support asthma care in light of constraints and disruptions to healthcare systems. We found no evidence regarding health inequalities, and this urgently needs to be addressed in the literature as the burdens of asthma and of COVID-19 are not equally distributed across the population.